Pengaruh Profitabilitas, Likuiditas dan Pertumbuhan Aktiva terhadap Keputusan Pendanaan pada Perusahaan Food And Beverage yang Terdaftar di Bursa Efek Indonesia - Surya Lestari, Ni Putu Indah (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The subsidizing choice may be a monetary choice related to obligation that must be made by the money related supervisor in a company. The proper financing choice will increment financing within the company's operational exercises. There are different components that can impact company subsidizing choices. In this inquire about, what impacts subsidizing choices is productivity, liquidity and resource development. The point of this inquire about is to decide the impact of productivity, liquidity and resource development on funding decisions. This investigate took a test of 11 companies recorded on the Indonesian Stock Trade within the Nourishment and Refreshments Sub Segment for the 2019-2021 period. Assurance of the test utilizing the purposive testing strategy. The expository apparatus utilized is different direct relapse. The results of this inquire about demonstrate that the productivity variable has an inconsequential negative impact on subsidizing choices. The liquidity variable features a critical negative impact on subsidizing choices, and the resource development variable has an inconsequential positive impact on subsidizing choices